Need a Simulation Technician? Try Your University's Engineering Internship Program - Kelly, Michelle; Hayes, C.; Abdipranoto, A. (2017)
© 2017 International Nursing Association for Clinical Simulation and Learning Supporting the initiation and uptake of simulation-based learning in university or hospital settings requires strategising for human as well as equipment resources. If activities require use of highly technical simulation and audiovisual equipment, faculty may be reticent to engage with the learning strategies that rely on managing “complex” equipment. Sourcing technical support can be an expensive component of simulation business plans. An alternate source of technical support can be realised from undergraduate engineering students. Insights are shared about the initiation and current status of a symbiotic partnership between two university faculties to meet respective needs for workplace experience and simulation technical support.